Larviculture and seed production of the silver pompano, Trachinotus blochii (Lacepede, 1801) for the first time in India - Abdul Nazar, A.K.; Jayakumar, R; Tamilmani, G; Sakthivel, M; Kalidas, C; Ramesh Kumar, P; Anbarasu, M; Sirajudeen, S; Balamurugan, V; Jayasingh, M; Gopakumar, G. (Indian Journal of Fisheries, 2012)
Larviculture and seed production protocols for the silver pompano Trachinotus blochii, which is one of the promising finfishspecies for brackishwater and marine aquaculture was developed based on six trials for the first time in India. The newlyhatched larvae were stocked at a density of 20 larvae l-1 in 2 t FRP tanks with 1.5 t of seawater. Green water technique wasemployed during larviculture upto the weaning period. Enriched S-type rotifers were fed at a density of 10-12 nos. ml-1 until3 day post hatch (dph) and the enriched L-type rotifers were given at a density of 6-8 nos. ml-1 from 7 dph and thereafter withenriched Artemia at a density of 3-5 nos. ml-1. Weaning started from 15 dph and by 20-25 dph metamorphosis was completed.The survival on completion of metamorphosis ranged from 10-15% and the specific growth rate in terms of length (mm) was8% per day. The larval morphology and growth pattern are also described.